Relationship of Age and Cavum Oris Volume in Children with Down Syndrome at Special School in Yogyakarta City - Rizki, Faisal; Bramanti, Indra; Titien Soeprihati, Indah (Jurnal Kesehatan Gigi, 2025)
Down syndrome is characterized by maxillary hypoplasia with a short and narrow palate, resulting in a smaller shape and volume of the oral cavity. Research findings by experts on the cavum oris volume of individuals with Down syndrome indicate differences due to genetic abnormalities, secondary causes,and age. This purpose of this study is to analyze the relationship between age and  cavum oris volume in children with Down Syndrome at the Special School in Yogyakarta City. An observational study with a cross-sectional approach was conducted on 28 children with Down syndrome at the Yogyakarta Special School who met the inclusion and exclusion criteria. The digital printing of the cavum oris is performed using Shining 3D Dental. Measurement of cavum oris volume using 3Shape 3DViewer and Inventor Professional 2020. The relationship between age and cavum oris volume was analyzed using statistical tests of correlation coefficients and T-tests with a 95% confidence level. The results show an R value of 0.942, which means there is a very strong positive correlation between increasing age and increasing cavum oris volume. The T-test shows that the age variable has a t-value of 3.967 with p=0.058 (p<0.05), indicating that the age variable does not have a significant effect on the volume of the cavum oris. The research conclusion is that in children with Down syndrome, the volume of the cavum oris increases with age, but this increase is not significant.